Specification for insulating and sheathing materials for cables. Cross-linked sheathing compounds having low emission of corrosive gases, and suitable for use in cables having low emission of smoke when affected by fire. Harmonized types Part 8.1, (15th November 2000) - British Standards Institution,
No abstract available